Optimalisasi Pengawasan CSR Perusahaan dalam Rangka Pencegahan Tindak Pidana Perdagangan Manusia pada Rantai Pasok Industri-industri - Karmenita Rosana Purba; Diki Zukriadi (LPPM Universitas Buddhi Dharma, 2026)
Corporate Social Responsibility (CSR) is a strategic instrument that not only functions as a form of corporate social responsibility, but also as a means of preventing various human rights violations, including human trafficking in the industrial supply chain. This study aims to analyze the role and effectiveness of CSR implementation supervision in preventing labor exploitation and human trafficking in the industrial sector, as well as identifying legal and policy challenges that hinder its implementation in Indonesia. The research method used is a normative juridical approach by examining related laws and regulations, legal doctrines, and case studies of companies with extensive supply chains. The results of the study indicate that CSR implementation oriented towards fulfilling the principle of human rights due diligence can be an early prevention mechanism against human trafficking practices. However, the weak government oversight system and the lack of company transparency in supply chain reporting cause the effectiveness of CSR to be less than optimal. Therefore, strengthening regulations and independent audit mechanisms are needed to ensure the integration of humanitarian aspects into companies' CSR policies. In conclusion, optimizing CSR oversight is a strategic step towards building an industrial ecosystem that is ethical, just, and free from human trafficking practices.